X+14=-4(x-1)

Simple and best practice solution for X+14=-4(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+14=-4(x-1) equation:


Simplifying
X + 14 = -4(x + -1)

Reorder the terms:
14 + X = -4(x + -1)

Reorder the terms:
14 + X = -4(-1 + x)
14 + X = (-1 * -4 + x * -4)
14 + X = (4 + -4x)

Solving
14 + X = 4 + -4x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -14 + X = 4 + -14 + -4x

Combine like terms: 14 + -14 = 0
0 + X = 4 + -14 + -4x
X = 4 + -14 + -4x

Combine like terms: 4 + -14 = -10
X = -10 + -4x

Simplifying
X = -10 + -4x

See similar equations:

| z-z(z+3)+3z= | | 0=4.9t^2+225.0 | | k(x^2+1)=x-k | | 56+6576=7563g+67757-5357476+456645gh | | 8(x+6)=8(x+15) | | 3(-5x-3)=-x-23 | | 4.7m=24.44 | | 15x-8y=128 | | 8x-6=48x-6 | | 6(a-6)=-6a-24 | | 3x-3x+10=1 | | 16x^10+2x^5+6=0 | | 7x+11=-7x-20 | | x/1/5-5=35 | | -7(5v-5)=280 | | .05x+.10(14-2x)+.25+(x+6)=3.3 | | 4+125x+5x^2=0 | | 7r^2+10r-8=0 | | 2x+26-7=x | | -4(1+7x)=-88 | | 4+125x+5t^2=0 | | 7(x+11)=7x+77 | | .25x+80-.50x=.40 | | 5x^6-2x^2+8=0 | | 3n+n-8=2n+4 | | 6q-p+8q-p= | | 3p+19=29-7p | | 8.02=3.1f-8.1 | | M-2=-16+3m | | Y=0.6-75 | | 7x-35-3x=4x-35 | | -2y^3(5xy^4)= |

Equations solver categories